Environmental Factors Affecting the Application of The Expanded Business Reporting Language (XBRL) in Commercial Banks Operating in The City of Benghazi - A Field Study - عبدالحفيظ عبد الدائم الشريف, طارق; عبدالسلام عبدالهادي زيد, عبدالحفيظ; محمد رمضان قرقوم, عبدالرؤوف; محمود محمد المغربي, فيصل (Dirasat in Economics and Business, 2026)
Current research examines measuring the applicability of expanded business report language (eXtensible Business Reporting Language (XBRL)) in Libyan commercial banks, and testing the role of environmental factors (regulatory, economic, legal, technical) in the applicability of the language in order to determine the type and magnitude of the impact of these factors and the requirements for their response and development to facilitate adoption of the business report language in the field of accounting work. From the benefits of language in developing and supporting accounting performance, research aims to study and analyses environmental factors and their contribution to supporting the applicability of expanded business report language in the environment of Libyan commercial banks. In this context, seven main hypotheses have been formulated, each of which has three sub-hypotheses, and these variables and relationships have been tested through the adoption of the survey methodology based on statistical analysis of the data collected through a questionnaire prepared for this purpose, which has been distributed to a sample of 73 individuals working in a group of Libyan commercial banks operating in Benghazi. The study›s data were analysed and its hypotheses tested using the modelling of structural equations in micro-squares using Smart PLS-SEM version 4. The study drew important conclusions, most notably the weak realities of environmental factors and thus its limited contribution to supporting the application of the language in Libyan commercial banks. The study also found the urgent need to apply the language as a result of its considerable benefits to all stakeholders. Therefore, the study recommends the necessity of adopting the XBRL language in Libyan commercial banks after carrying out the necessary development in qualifying the aspects of the environmental factors affecting the elements supporting its successful application.